Students' Sexual Orientations, Self-Esteem, and Problems - Convocar, Jeremias; Pios, Myrna (JPAIR Multidisciplinary Research, 2019)
Creating a safe and supportive learning environment for all students regardless of their sexual orientations is especially important. This descriptive study determined the extent of sexual orientations, level of self-esteem and problems of 664 randomly selected senior college students of a certain state university in the Philippines. The online Epstein Sexual Orientation Inventory (Epstein, McKinney, Fox, & Garcia, 2012), Rosenberg (1989) Self-esteem scale, and Mooney (in Tian & Heppner, 2018) Problem Check Lists were employed in the study. The findings revealed that of 664 college students, 56 % were “straight,” 38 % were “bisexual,” 6 % were “homosexual”; of 300 males, 57 % were “straights”, 33% were “bisexuals”, and 9% were “gays”; of 364 females, 55% were straights, 42% were “bisexuals”, and 4% were “lesbians”. They had “high” self-esteem regardless of their sexual orientations; male-bisexuals had significantly better self-esteem than male-gays. Generally, they need concentration in studying academics and enough rest, worried about how to get a job after graduation and economic condition of their parents, personal financial needs, social leadership qualities, and spiritual assurance. However, gays and lesbians need more freedom and most obsessed with emotional and sexual life. Thus, higher education institutions should provide to all students a wholesome and supportive learning environment responsive to students’ individual needs and well-being regardless of sexual orientations.
Keywords: Sexual Orientations; Self-esteem; Problems; College Students; HEI; Philippines